Conceptualizing and Mapping Geocultural Space. Issue 2 (October 2015) - Stadler, Jane
Abstract : This essay seeks to critically conceptualize the term geocultural space and the emerging field of study with which it is associated by exploring the various ways in which such space is currently being mapped by researchers using digital humanities tools and methods. In drawing together intersecting interests in Geographic Information Systems and spatio-cultural narratives and experiences, this work defines an interdisciplinary field of research that is gathering momentum as geolocative technologies that shape and reshape the ways in which we perceive and experience the world become increasingly prevalent in academic life and in the cultural mainstream.